Application to the Port of Sines of a new tool for risk assessment in port navigation - Neves, D. R. (2013)
This paper describes a first approach on the risk assessment in port navigation using GUIOMAR, an integrated system for port and coastal engineering modelling developed at the National Civil Engineering Laboratory (LNEC), Portugal, using a GIS software environment. A set of automatic procedures was designed to include a new methodology based on the amplitude of the wave-induced vertical movement of a ship along its trajectory. In this methodology, the risk in port navigation is assessed on the basis of a combination of the probability of exceedance of a pre-set threshold for the ship’s vertical movements and its consequences. To test the new procedures, a set of sea wave records obtained at the Sines wave-buoy from 1988 to 2002 was transferred into Sines Port using two numerical models of sea wave propagation and deformation (SWAN and DREAMS), included in the GUIOMAR system. The numerical model WAMIT was used for estimating the wave-induced ship’s vertical movements inside the port. By applying the new procedures, automatic generation of risk maps was carried out for navigation in the vicinity of theWest breakwater of the Port of Sines. The recent developments contribute towards a more versatile and efficient GUIOMAR system, which results in a more adequate tool to support decision-making processes in port and coastal management